Second-Line Intravesical Therapy. What is the Present Role of Device-Assisted Therapy?. Issue 21 (January 2013) - Racioppi, Marco; D'Agostino, Daniele; Di Gianfrancesco, Luca; Bassi, Pier Francesco
Non-muscle-invasive bladder cancer is a common urinary malignancy whose management is a challenge: strong evidence supports the use of passive intravesical chemotherapy in the management of this tumor. Despite current guidelines, the treatment is suboptimal as illustrated by the high risk of recurrence and progression. Bacillus Calmette-Guérin (BCG) is the gold standard for the treatment of high-grade non-muscle-invasive bladder cancer, but in case of disease persistence, after 2 consecutive induction courses of BCG, patients must undergo radical cystectomy. We discuss options for second-line adjuvant therapy for non-muscle-invasive bladder cancer in standard treatment non-responder patients. We investigated the use and application of device-assisted therapy for the intravesical treatment of bladder cancer, such as thermochemotherapy (TCT) and electromotive drug administration (EMDA). Many studies demonstrate their synergistic therapeutic effect, greater than the single treatment with chemotherapy, inducing an increased absorption of the chemotherapeutic agent (Mitomycin C) to the urothelium. TCT and EMDA are safe and effective in terms of outcomes. For the future it will be important to encourage the use of the existing technology within the appropriate clinical indications.